The stepsisters [compact disc, unabridged] - Mallery, Susan (Harlequin Audio, 2021)
When her dad married Sage's mom, Daisy was thrilled to get a new sister. But Sage was beautiful and popular, everything Daisy was not, and she made sure Daisy knew it. Sage didn't have Daisy's smarts, she had to go back a grade to enroll in the fancy rich-kid school. So she used her popularity as a weapon, putting Daisy down to elevate herself. After the divorce, the stepsisters' rivalry continued until the final, improbable straw: Daisy married Sage's first love. Eighteen years, two kids, and one troubled marriage later, Daisy never expects, or wants, to see Sage again. But when the little sister they have in common needs them both, they put aside their differences to care for Cassidy. As long-buried truths are revealed, no one is more surprised than they when friendship blossoms. Their fragile truce is threatened by one careless act that could have devastating consequences. They could turn their backs on each other again, or they could learn to forgive once and for all.